Ophthalmology practice in the era of COVID-19 : a personal reflection from a Sarawakian Ophthalmologist - Lim, Lik Thai (College of Ophthalmologists, Academy of Medicine of Malaysia, 2020)
When COVID-19 first gained international mentioned back in December 2019 (at that time it was first referred to as the ‘Wuhan virus’), never would I imagine that this problem will become such a menacing international pandemic affecting almost the entire world population and claiming hundreds of thousands of lives thus far.